Enterprise process modelling complemented with business rules. (27th October 2011) - Barjis, Joseph
Expectations of the 21st century enterprise are, first of all, coping with complexity of modern business settings, dynamicity of business environment, and possessing corresponding flexibility . These expectations require rigid, explicit, and precise definition and description of business rules . To identify, define and incorporate business rules into the enterprise business process models, it is needed to design an ontological model (construction-oriented model) of an enterprise, where the white-box system approach is applied. The white-box approach allows capturing not only each action, but also the actors (actor roles) and their interactions. In this article, the focus is on two important components of enterprise process modelling. The first component is the construction-oriented (platform and realisation independent) ontological models. The second component is rules-based description of business processes. These two components are put together as an integrated method for rules complemented enterprise process modelling. For illustration, an example of patient examination process is discussed, where first an enterprise process model is developed, then the model is further complemented with business rules.